Analisis Kekuatan Tarik Material Komposit Berpenguat Ampas Pengolahan Sagu - Saleh, La Ode Muhamad; Samhuddin, Samhuddin; Aksar, Prinob (Teknik Mesin Universitas Halu Oleo, 2022)
In the industrial world, the development of material technology is growing rapidly. Various kinds of materials have been used and further research is being carried out to obtain the right materials, one of which is composite materials. The purpose of this study was to determine the effect of the tensile strength of the composite material reinforced with sago pulp. In this study, the manufacture of composites using the hand lay up method. then the fiber is given alkaline treatment by soaking in a solution of NaOH (Sodium Hydroxide) with a concentration of 5% for 1 hour, 2 hours and without treatment. From the results obtained, immersion for 1 hour has the highest tensile stress of 10,456 N/mm², followed by immersion for 2 hours of tensile stress of 7.189 N/mm². While without treatment has the lowest tensile stress of 4.955 N/mm². This shows that the treatment will affect the tensile stress.Kata kunci: Sago drgs,tensile strength,alkali